Formação de lipídeos e produção de ácido γ-linolênico por Mucor circinelloides e Rhizopus sp., em óleos vegetais - Tauk-Tornisielo, Sâmia M. [UNESP]; Arasato, Luciana S. [UNESP]; de Almeida, Alex F. [UNESP]; Govone, José S. [UNESP]; Malagutti, Eleni N. [UNESP] (FapUNIFESP (SciELO), 2009)
The fungi strains were tested in Bioscreen automated system to select the best nutritional source. Following, shaking submserse cultures were studied in media containing sole carbon or nitrogen source. The growth of these strains improved in media containing vegetable oil, with high concentration of lipids. The high concentration of γ-linolenic acid was obtained with M. circinelloides in culture containing sesame oil.
Lipid formation and γ-linolenic acid production by Mucor circinelloides and Rhizopus sp., grown on vegetable oil
Keywords: Automated system; Liquid culture; Vegetable oils; Zigomycetes; γ-linolenic acid